The Effectiveness of Aquatic Exercises in the Treatment of Rheumatoid Arthritis - Tuncay Çakır; Fatma Deniz Evcik; Volkan Subaşı; İlknur Yiğit Gökçe; Vural Kavuncu (Galenos Yayinevi, 2014)
Objective: Rheumatoid Arthritis (RA) is a chronic destructive inflammatory disorder. This study is aimed to investigate the effects of balneotherapy and aquatherapy in the treatment of RA patients. Materials and Methods: A total of 59 patients who fulfilled the American College of Rheumatology diagnostic criteria for RA were included this study. Patients were randomly assigned into three groups. Group 1 (n=20) received balneotherapy, group 2 (n=20) received an aquatic exercise program and group 3 (n=19) was accepted as control group. These programs were applied five times a week, over three weeks (15 sessions). Patients were evaluated for clinical and laboratory parameters. Clinical parameters included pain,duration of morning stiffness, number of swollen and tender joints, disease activity score (DAS28), Modified health assessment questionnaire (mHAQ), physician's and patient's global assessment and hand grip strength. Laboratory evaluation included erythrocyte sedimentation rate(ESR) and C-reactive protein (CRP). The assessment parameters were measured before, at the end of and after 3 months of the therapy. Results: The mean age of the patients was 54±10.7 (25-75) years and the mean disease duration was 122.3±98.1 (1-424) months. In aquatic exercise group we observed an improvement in DAS28 scores (p<0.001), in the number of tender joints (p<0.005), in VAS scores (p<0.005), mHAQ (p<0.05), physician's and patient's global assessments (p<0.05). Also there was a statistically significant decrease in ESR results in aquatherapy group compared to other groups (p<0.05). However no statistically significant difference was obtained between three groups (p>0.05). Conclusion: This study shows that aquatic exercise program is beneficial in the management of DAS28, pain, HAQ parameters and should be taken in to consideration in planning exercise therapy for RA patients. (Turkish Journal of Osteoporosis 2014;20: 10-5)